International Prosthodontics: Two Decades of Discussion - James Dudley (Faculty of Dentistry, Trisakti University, 2018)
Background: The perception that the specialty of prosthodontics has changed over time is subjective and largely based on personal belief, with little data to uphold this view in the literature. Objectives: The aim of this study was to compare the frequency of presentation categories at each International College of Prosthodontists Conference from 1999 to 2017 and identify trends. Methods: Available ICP Conference Programs were sourced from the ICP Administration and the titles of all presentations reviewed and catalogued into one of 13 presentation categories. The number of presentations in each category was expressed as a percentage of the total number of presentations for each conference and statistically analyzed for trends throughout the study period. Results: 69.61% of all presentations from all conferences were categorized as one of implant dentistry; materials, CAD-CAM and digital technologies; removable prosthodontics and edentulism; or fixed prosthodontics. 46.38% were categorized as implant dentistry or materials, CAD-CAM and digital technologies. The frequency of presentations of fixed prosthodontics significantly decreased while the frequency of implant dentistry; maxillo-facial prosthodontics; geriatric dentistry and medically compromised patients; and clinical case presentations and treatment planning significantly increased (p<0.05) over the study period. Conclusion: The ICP Conference presentation titles reviewed from 1999 to 2017 maintained a focus on implant dentistry and materials, CAD-CAM and digital technologies alongside a diverse range of other topics. Throughout the study period, the frequency of presentations of fixed prosthodontics significantly decreased while the frequency of presentation of implant dentistry; maxillo-facial prosthodontics; geriatric dentistry; and clinical case presentations and treatment planning significantly increased.